Micro-arc oxidation coating on surface of magnesium / aluminum or magnesium / aluminum alloy composite material as well as preparation method and application of micro-arc oxidation coating

Through the combined microarc oxidation treatment process of low voltage passivation and high voltage growth, the problem of ablation and rupture of the film layer at high voltage is solved, and the uniform thickness and high hardness of the film layer are achieved, which significantly improves the corrosion resistance of the material.

CN119530918APending Publication Date: 2025-02-28CENT SOUTH UNIV

Patent Information

Application Number
CN202411689115.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Magnesium/aluminum composites are prone to galvanic corrosion problems during use, and existing microarc oxidation technologies can easily lead to ablation, rupture or uneven growth of the film layer under high voltage.

Method used

A combined microarc oxidation treatment process of low voltage passivation and high voltage growth is adopted to form a silica coating on the surface of magnesium/aluminum composite materials, and combined with the differences in voltage responses of different metals, uniform growth and high hardness of the film layer are achieved.

Benefits of technology

It effectively solves the problems of ablation and rupture of the film layer under high voltage of magnesium/aluminum composite materials, realizes the uniform thickness and high hardness of the film layer, and significantly improves the corrosion resistance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530918A_ABST
    Figure CN119530918A_ABST
Patent Text Reader

Abstract

The invention discloses a micro-arc oxidation coating on the surface of a magnesium / aluminum or magnesium / aluminum alloy composite material as well as a preparation method and application of the micro-arc oxidation coating. Belongs to the technical field of metal surface micro-arc oxidation corrosion prevention, and is a micro-arc oxidation coating formed by carrying out low-voltage passivation and high-voltage growth multi-step micro-arc oxidation treatment on the surface of a magnesium / aluminum or magnesium / aluminum alloy composite material. According to the method, the passivation layer which is relatively thin but relatively compact is prepared at low voltage, so that the metal surface activity is reduced, and the oxide film layer is prevented from being ablated and broken under subsequent high-voltage treatment; according to different response conditions of different metals to the same voltage and the growth characteristics of the micro-arc oxidation coating, the coatings on different metal sides can grow to 100 microns in a low-voltage and high-voltage combined treatment mode. The problems that the damaged part of the magnesium alloy is repaired by using aluminum and an alloy thereof, galvanic corrosion occurs in a magnesium / aluminum composite board and a magnesium / aluminum composite component in the service process, the properties of a low-voltage film layer of a composite metal material are uneven, and a high-voltage film layer is ablated and damaged are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of micro-arc oxidation anti-corrosion on metal surfaces, and specifically relates to a micro-arc oxidation coating on the surface of a magnesium / aluminum or alloy composite material thereof, and a preparation method and application thereof. Background Art

[0002] Due to its low density, high specific strength, excellent processing performance and shock absorption performance, magnesium alloys have replaced traditional structural metal materials in the fields of transportation, automobiles / trains / bicycles, 3C products, aerospace, machinery, ships, etc., and have extremely important application value in reducing the weight of equipment structures. However, magnesium alloy structural parts made of a single material may not meet the multiple performance requirements of structural materials in various fields due to the poor corrosion resistance of magnesium alloys, poor plastic forming ability, or failure to meet higher mechanical performance requirements. Therefore, magnesium alloys are usually processed into composite materials or composite components with other alloys for use. For example, layered composite metal sheets such as aluminum / magnesium / aluminum and magnesium / aluminum are prepared by rolling or explosion welding, and magnesium alloys are connected to aluminum alloy materials by self-piercing riveting or stir friction welding, melting welding, etc. to form heterogeneous alloy components. For magnesium alloy components, after corrosion holes, cracks and other defects appear on the surface, they are usually filled and repaired with aluminum alloys by spraying, melting welding, etc., thereby forming magnesium / aluminum heterogeneous composite materials. For magnesium / aluminum heterogeneous metal composites, in addition to the wear resistance and corrosion resistance of the magnesium alloy and aluminum alloy, special attention should be paid to the contact between magnesium and aluminum heterogeneous metals to form a primary battery, which will inevitably lead to galvanic corrosion and accelerate the corrosion failure process of metal composites. Preparing a coating on the surface of heterogeneous metal composites to isolate the corrosive medium is an effective means to improve the corrosion resistance. Common surface treatment methods include electroplating, chemical plating, anodizing, micro-arc oxidation, etc.

[0003] Among them, micro-arc oxidation (MAO) is an environmentally friendly surface treatment technology that can generate ceramic coatings with high bonding strength, thickness and hardness on the surface of valve metals such as aluminum alloys, magnesium alloys and titanium alloys. Conventional micro-arc oxidation electrolyte systems usually use one of silicates, phosphates and aluminates as the main salts, and different additives are usually added according to the performance requirements of the coating. At present, there are far fewer articles and patents on micro-arc oxidation treatment of heterogeneous alloy materials than single alloys. On the one hand, different alloy substrates respond differently to the same current and voltage input. The arc starting voltage of magnesium alloys is lower than that of aluminum alloys and titanium alloys, and the film grows more rapidly, which is easy to break under high voltage input; on the other hand, different anions have different abilities to form passivation layers on different metals. For example, on magnesium alloys, silicate is the strongest, phosphate is the second, and aluminate is the worst. In addition, the pH value of the electrolyte of magnesium alloys is usually lower than that of aluminum alloys. How to eliminate the differences in electrolytes and electrical control parameters caused by different properties of the base metal has become a difficult problem in micro-arc oxidation of heterogeneous alloys. Patent 201510207720.X prepared a ceramic coating on an aluminum / titanium composite plate, but the coatings of the aluminum plate and the titanium plate have different compositions, and cannot provide uniform protection for the composite plate as a whole under working conditions. Patent 202310236235.X provides a method for preparing an amorphous silicon dioxide coating based on micro-arc oxidation and conducts tests on magnesium alloys and aluminum alloys to confirm the versatility of the electrolyte. However, the electrolyte still does not achieve uniformity in electrical control parameters on magnesium alloys and aluminum alloys.

[0004] Based on the above existing background, the present invention is proposed. Summary of the invention

[0005] The purpose of the present invention is to provide a micro-arc oxidation film layer on the surface of aluminum / magnesium composite material by using micro-arc oxidation technology, which is a combination of low-voltage passivation and high-voltage growth micro-arc oxidation treatment process, and its preparation method and application. It can solve the problems of repairing the damaged part of magnesium alloy by using aluminum and its alloys, galvanic corrosion of aluminum / magnesium composite plates and aluminum / magnesium composite components during service, and uneven properties of low-voltage film layers of composite metal materials and ablation and damage of high-voltage film layers.

[0006] The technical solution of the present invention to solve the above technical problems is as follows:

[0007] A micro-arc oxidation coating on the surface of a magnesium / aluminum or alloy composite material, wherein the micro-arc oxidation film layer comprises silicon dioxide; the micro-arc oxidation film layer on the surface of aluminum or aluminum alloy has a thickness of 10 to 130 μm and a hardness of 400 to 1200 HV; the micro-arc oxidation film layer on the surface of magnesium or magnesium alloy has a thickness of 10 to 135 μm and a hardness of 400 to 1200 HV.

[0008] The magnesium / aluminum or its alloy composite material is prepared by welding or thermal spraying with magnesium alloy as the matrix and pure aluminum or aluminum alloy as the repair metal, or by plastic deformation such as welding or rolling of magnesium alloy, pure aluminum or aluminum alloy, mechanical connection, etc.

[0009] Furthermore, the micro-arc oxidation coating is formed by performing a multi-step micro-arc oxidation treatment of low voltage passivation and high voltage growth on the surface of the magnesium / aluminum or its alloy composite material.

[0010] The present invention also provides a method for preparing the micro-arc oxidation coating on the surface of the magnesium / aluminum or its alloy composite material, comprising the following steps:

[0011] 1) grinding, cleaning, and drying the magnesium / aluminum or its alloy composite material workpiece for standby use;

[0012] 2) The electrolyte contains sodium hydroxide, tetraethyl silicate and an additive; the additive includes at least one of fluoride salt, fluorotitanate and sodium phosphate;

[0013] 3) Micro-arc oxidation treatment:

[0014] a) Low voltage passivation;

[0015] b) High voltage growth.

[0016] The micro-arc oxidation treatment in a) and b) includes a one-step treatment, or a step-by-step pressure-boosting treatment by only changing the voltage;

[0017] The voltage span of the segmented or stepped treatment is at least 20V; the stepped treatment refers to the treatment by only increasing the forward voltage step by step; the segmented treatment refers to the change of parameters such as frequency and duty cycle in addition to increasing the forward voltage step by step;

[0018] The treatment time of each section of the segmented treatment is 1 to 15 minutes, and the treatment time of each section of the step-type treatment is 1 to 15 minutes; if a) and b) adopt segmented and step-type treatment, each section should be at least 2 sections; after high voltage growth, voltage reduction repair can be carried out according to actual conditions;

[0019] The electrolyte temperature is not higher than 45°C during the micro-arc oxidation process.

[0020] Further,

[0021] Step 1) During the workpiece pretreatment, the magnesium / aluminum or alloy composite material workpiece is polished step by step with sandpaper to remove surface processing marks, and is ultrasonically cleaned in anhydrous ethanol for at least 6 minutes and blown dry for later use.

[0022] Step 2) When preparing the electrolyte, the concentration of sodium hydroxide is 5-50g / L, the concentration of tetraethyl silicate is 10-250ml / L, the solute addition order should be sodium hydroxide, tetraethyl silicate, and stirring should be maintained during the addition process; the solution should be continuously stirred for 1-12h after preparation; the concentration of the additive does not exceed 40g / L.

[0023] Step 3) Micro-arc oxidation treatment:

[0024] a) Low voltage passivation: forward voltage 50~480V, negative voltage 0~200V, current density 1~20A / dm 2 , frequency is 50~5000Hz, duty cycle is 5%~50%, positive and negative pulse number ratio is (1~10):(0~10), processing time is 3~30min; positive and negative directions adopt constant voltage or constant current mode output;

[0025] b) High voltage growth: forward voltage 400-600V, negative voltage 0-200V, current density 1-20A / dm 2 , frequency is 50~5000Hz, duty cycle is 5%~50%, the ratio of positive and negative pulse numbers is (1~10):(0~10), processing time is 3~30min; positive and negative directions adopt constant voltage or constant current mode output.

[0026] Voltage reduction repair: forward voltage 300~500V, negative voltage 0~200V, current density 1~20A / dm 2 , frequency is 50~5000Hz, duty cycle is 5%~50%, the ratio of positive and negative pulse numbers is (1~10):(0~10), processing time is 3~30min; positive and negative directions adopt constant voltage or constant current mode output.

[0027] The voltage of the micro-arc oxidation treatment in the above-mentioned step-down repair should be at least 100V lower than the highest voltage in b);

[0028] Pressure reduction repair is a process in which silicon-containing anion groups are adsorbed on the pores of the membrane layer under the action of an electric field and dehydrated to repair the membrane layer. This treatment is an optional step.

[0029] The present invention also provides application of the micro-arc oxidation coating on the surface of the magnesium / aluminum or alloy composite material in metal corrosion protection.

[0030] The metal includes magnesium / aluminum or alloy composite materials thereof.

[0031] The micro-arc oxidation film sample obtained by the method of the present invention should be ultrasonically cleaned with deionized water and naturally air-dried or blow-dried.

[0032] The main differences between the present invention and the prior art are as follows: 1. The electrolyte of the prior art uses one of phosphate, aluminate and silicate as the main salt, selects a variety of inorganic or organic substances as additives, and the prepared film layer is mostly oxides related to the base metal and the additives. The electrolyte of the present invention is an organic silicon electrolyte, and the prepared film layer component is silicon dioxide, which has stronger and more stable corrosion resistance than metal oxides, and basically does not consume the base metal; 2. The film layer prepared by the prior art is usually discontinuous at the interface of the heterogeneous alloy connection, which is reflected in the thickness and structure of the film layer, and cracks are prone to occur. The oxide layer prepared by the present invention is well bonded at the interface without cracks, and the thickness is basically 3. The difference in thickness of the oxide layers prepared on the surfaces of both sides of the dissimilar alloys in the prior art is small only when the film layer is thin, and the thickness difference increases with the increase in the overall thickness of the film layer. In addition, the one-step micro-arc oxidation treatment is prone to cause ablation, rupture or uneven growth of the film layer on the metal surface on one side under high voltage conditions. The present invention prepares a thin but relatively dense passivation layer at low voltage to reduce the metal surface activity and avoid ablation and rupture of the oxide film layer under subsequent high voltage treatment; utilizing the different responses of different metals to the same voltage and the growth characteristics of the micro-arc oxidation coating, the coatings on different metal sides can be grown to 100μm through a combination of low voltage and high voltage treatment.

[0033] The core process of the present invention is a combined treatment method of low-voltage passivation and high-voltage growth. Low-voltage passivation refers to growing a thinner oxide layer on both sides or one side of a metal composite plate through single-step or multi-step micro-arc oxidation treatment; high-voltage growth refers to gradually thickening the oxide layer on both sides of the metal composite plate to a uniform thickness standard through single-step or multi-step micro-arc oxidation treatment. In each embodiment of the present invention, multi-stage boosting treatment is the core process, and subsequent voltage reduction treatment can be deleted according to actual needs or effects. It should be pointed out that for aluminum / magnesium composite plates or components using silicone solution as the electrolyte, both segmented or stepped boosting treatment processes can be variations.

[0034] Beneficial Effects

[0035] 1. The present invention adopts micro-arc oxidation technology to prepare the ceramic coating, the coating is well bonded to the substrate, and the coating grown on the substrate of the dissimilar alloy at the weld is densely bonded without obvious cracks.

[0036] 2. The micro-arc oxidation coating of the present invention has uniform composition and good stability. The coating thickness on different substrates can be regulated by adjusting the processing steps and parameters to achieve a substantially consistent thickness or a target thickness.

[0037] 3. The micro-arc oxidation coating of the present invention is based on a magnesium / aluminum composite plate material, which can provide certain guidance for the surface anti-corrosion treatment process of heterogeneous alloy composite materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 : Surface macroscopic morphology of comparative example 1;

[0039] Figure 2 : Surface macroscopic morphology of Example 1;

[0040] Figure 3 : Cross-sectional morphology of Example 1;

[0041] Figure 4 : Surface macroscopic morphology of Example 2;

[0042] Figure 5 : Cross-sectional morphology of Example 2;

[0043] Figure 6 : Surface macroscopic morphology of Example 3;

[0044] Figure 7 : Surface microscopic morphology of Example 3;

[0045] Figure 8 : Cross-sectional morphology of Example 3;

[0046] Fig. 9 : Cross-sectional EDS spectrum of Example 3. DETAILED DESCRIPTION

[0047] The following examples are intended to further illustrate the present invention, but are not intended to limit the present invention.

[0048] Comparative Example 1

[0049] 1. Pretreatment: Cut the composite sheet into 20mm×15mm×2mm rectangles, then polish it step by step with sandpaper to 2000#, and ultrasonically clean it with anhydrous ethanol, blow dry and set aside.

[0050] 2. Prepare the electrolyte: add deionized water, sodium hydroxide, and tetraethyl silicate (TEOS) in a molar ratio of 86:1:1 in sequence, add sodium hydroxide and continue stirring until it becomes clear; then add tetraethyl silicate and continue stirring for 8 hours for use.

[0051] 3. Micro-arc oxidation treatment: stainless steel plate is used as cathode, aluminum / magnesium explosion welding sample is used as anode and immersed in electrolyte. The output mode is constant voltage output, the frequency is 800Hz, the forward voltage is 500V, the positive and negative duty cycles are both 5%, the processing time is 8min, and no negative loading is performed. During the micro-arc oxidation process, the electrolyte temperature is kept below 45°C.

[0052] 4. Post-processing: Use deionized water for ultrasonic cleaning for 6 minutes and then blow dry.

[0053] The aluminum / magnesium explosion welding micro-arc oxidation sample was obtained through the above steps. The magnesium alloy side of the magnesium / aluminum alloy sample could not withstand a higher voltage under the one-step micro-arc oxidation treatment, and the coating at this time had serious macroscopic defects.

[0054] Example 1

[0055] 1. Pretreatment: Cut the composite sheet into 20mm×15mm×2mm rectangles, then polish it step by step with sandpaper to 2000#, and ultrasonically clean it with anhydrous ethanol, blow dry and set aside.

[0056] 2. Prepare the electrolyte: add deionized water, sodium hydroxide, and tetraethyl silicate (TEOS) in a molar ratio of 86:1:1 in sequence, add sodium hydroxide and continue stirring until it becomes clear; then add tetraethyl silicate and continue stirring for 8 hours for use.

[0057] 3. Micro-arc oxidation processing: The stainless steel plate is used as the cathode, and the aluminum / magnesium explosion welding sample is used as the anode and immersed in the electrolyte. Micro-arc oxidation treatment is a two-step process.

[0058] 1) Step 1: The output mode is constant voltage output, the frequency is 200Hz, the forward voltage is 300V, the positive and negative duty cycles are both 10%, the processing time is 5min, and no negative loading is performed;

[0059] 2) Step 2: The output mode is constant voltage output, the frequency is 600Hz, the forward voltage is 450V, the positive and negative duty cycles are both 15%, the processing time is 5min, and no negative loading is performed;

[0060] 3) Keep the electrolyte temperature below 45°C during micro-arc oxidation.

[0061] 4. Post-processing: Use deionized water for ultrasonic cleaning for 6 minutes and then blow dry.

[0062] The aluminum / magnesium explosive welding micro-arc oxidation sample was obtained through the above steps. The aluminum alloy part of the film layer was composed of amorphous silicon dioxide, with a thickness of 25.1 μm. The aluminum alloy side film layer of Example 1 was too thin to perform Vickers hardness test; the magnesium alloy part of the film layer was composed of amorphous silicon dioxide, with a thickness of 113.6 μm and a hardness of 460.68 HV. The test results showed that the difference in thickness between the two parts of the film layer at the weld was about 44.7 μm.

[0063] Example 2

[0064] 1. Pretreatment: Cut the composite sheet into 20mm×15mm×2mm rectangles, then polish it step by step with sandpaper to 2000#, and ultrasonically clean it with anhydrous ethanol, blow dry and set aside.

[0065] 2. Prepare the electrolyte: add deionized water, sodium hydroxide, and tetraethyl silicate (TEOS) in a molar ratio of 86:1:1 in sequence, add sodium hydroxide and continue stirring until it becomes clear; then add tetraethyl silicate and continue stirring for 8 hours for use.

[0066] 3. Micro-arc oxidation processing: The stainless steel plate is used as the cathode, and the aluminum / magnesium explosion welding sample is used as the anode and immersed in the electrolyte. The micro-arc oxidation treatment is a three-step process.

[0067] 1) Step 1: The output mode is constant voltage output, the frequency is 200Hz, the forward voltage is 350V, the positive and negative duty cycles are both 10%, the processing time is 5min, and no negative loading is performed;

[0068] 2) Step 2: The output mode is constant voltage output, the frequency is 800Hz, the forward voltage is 500V, the positive and negative duty cycles are both 5%, the processing time is 5min, and no negative loading is performed;

[0069] 3) Step 3: The output mode is constant voltage output, the frequency is 800Hz, the forward voltage is 400V, the positive and negative duty cycles are both 5%, the processing time is 5min, and no negative loading is performed;

[0070] 4) Keep the electrolyte temperature below 45°C during micro-arc oxidation.

[0071] 4. Post-processing: Use deionized water for ultrasonic cleaning for 6 minutes and then blow dry.

[0072] The aluminum / magnesium explosive welding micro-arc oxidation samples were obtained through the above steps. The aluminum alloy part of the film layer was composed of amorphous silicon dioxide, with a thickness of 100.63μm and a hardness of 452.32HV; the magnesium alloy part of the film layer was composed of amorphous silicon dioxide, with a thickness of 115.85μm and a hardness of 533.17HV. The difference in thickness of the two parts of the film at the weld was 21.4μm.

[0073] Example 3

[0074] 1. Pretreatment: Cut the composite sheet into 20mm×15mm×2mm rectangles, then polish it step by step with sandpaper to 2000#, and ultrasonically clean it with anhydrous ethanol, blow dry and set aside.

[0075] 2. Prepare the electrolyte: add deionized water, sodium hydroxide, and tetraethyl silicate (TEOS) in a molar ratio of 86:1:1 in sequence, add sodium hydroxide and continue stirring until it becomes clear; then add tetraethyl silicate and continue stirring for 8 hours for use.

[0076] 3. Micro-arc oxidation processing: The stainless steel plate is used as the cathode, and the aluminum / magnesium explosion welding sample is used as the anode and immersed in the electrolyte. The micro-arc oxidation treatment is a four-step process.

[0077] 1) Step 1: The output mode is constant voltage output, the frequency is 200Hz, the forward voltage is 300V, the positive and negative duty cycles are both 10%, the processing time is 5min, and no negative loading is performed;

[0078] 2) Step 2: The output mode is constant voltage output, the frequency is 600Hz, the forward voltage is 350V, the positive and negative duty cycles are both 25%, the processing time is 5min, and no negative loading is performed;

[0079] 3) Step 3: The output mode is constant voltage output, the frequency is 800Hz, the forward voltage is 500V, the positive and negative duty cycles are both 10%, the processing time is 5min, and no negative loading is performed;

[0080] 4) Step 4: The output mode is constant voltage output, the frequency is 1000Hz, the forward voltage is 400V, the positive and negative duty cycles are both 5%, the processing time is 5min, and no negative loading is performed;

[0081] 5) Keep the electrolyte temperature below 45°C during micro-arc oxidation.

[0082] 4. Post-processing: Use deionized water for ultrasonic cleaning for 6 minutes and then blow dry.

[0083] The aluminum / magnesium explosive welding micro-arc oxidation samples were obtained through the above steps. The aluminum alloy part of the film layer was composed of amorphous silicon dioxide, with a thickness of 82.83μm and a hardness of 527.6HV; the magnesium alloy part of the film layer was composed of amorphous silicon dioxide, with a thickness of 112.37μm and a hardness of 569.32HV. The thickness of the two parts of the film at the weld was basically consistent, which was 106.0±0.5μm.

[0084] From the macroscopic surface morphology and cross-sectional morphology of the samples obtained in Comparative Example 1, Example 1, Example 2 and Example 3, and the surface scanning electron microscope image of Example 3, it can be seen that the oxide layer without macroscopic defects can be grown on the aluminum alloy side of the sample treated by one-step micro-arc oxidation, while the oxide layer obtained on the magnesium alloy side is of poor quality, grows unevenly, and has the phenomenon of film ablation, cracking and shedding, as shown in FIG. Figure 1 Example 1 is a sample of the low voltage passivation process of the present invention. The oxide film layers on both sides of the magnesium and aluminum are complete and relatively uniform. However, from the cross-sectional morphology diagram, it can be seen that the thickness of the oxide layers on both sides of the magnesium and aluminum varies little and is relatively dense. However, the thickness difference on both sides can reach 44.7μm. Figure 2 ,3. The samples obtained in Example 2 and Example 3 were all subjected to low voltage passivation and high voltage growth processes. After the low voltage micro-arc oxidation treatment, the surface activity of the samples was reduced, and the surface coating on the magnesium side was able to withstand a higher voltage. While the oxide layer on the aluminum side was growing, no ablation, cracking, or shedding occurred. Figure 4, 6 and 7. By comparing the cross-sectional views of the samples obtained in Example 2 and Example 3, it can be found that the film layer of the sample treated with two sections of low voltage is relatively denser and has a higher hardness, and the thickness and structure of the oxide film layer at the weld are smaller. Figure 5 and 8 The chemical composition of the magnesium side surface coating is slightly different from that of the aluminum side surface coating. The main components are silicon and oxygen. Figure 7 and 9 .

Claims

1. A micro-arc oxidation coating on the surface of a magnesium / aluminum or alloy composite material, characterized in that: The micro-arc oxidation film layer is composed of silicon dioxide; the thickness of the micro-arc oxidation film layer on the surface of aluminum or aluminum alloy is 10-130μm, and the hardness is 400-1200HV; the thickness of the micro-arc oxidation film layer on the surface of magnesium or magnesium alloy is 10-135μm, and the hardness is 400-1200HV.

2. The micro-arc oxidation coating on the surface of the magnesium / aluminum or alloy composite material according to claim 1, characterized in that: The magnesium / aluminum or its alloy composite material is prepared by welding or thermal spraying with magnesium alloy as the matrix and pure aluminum or aluminum alloy as the repair metal, or by plastic deformation such as welding or rolling of magnesium alloy, pure aluminum or aluminum alloy, mechanical connection, etc.

3. The micro-arc oxidation coating on the surface of the magnesium / aluminum or alloy composite material according to claim 1, characterized in that: The micro-arc oxidation coating is formed by performing low-voltage passivation and high-voltage growth multi-step micro-arc oxidation treatment on the surface of magnesium / aluminum or its alloy composite material.

4. The method for preparing a micro-arc oxidation coating on the surface of a magnesium / aluminum or alloy composite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: 1) grinding, cleaning, and drying the magnesium / aluminum or its alloy composite material workpiece for standby use; 2) The electrolyte contains sodium hydroxide, tetraethyl silicate and an additive; the additive includes at least one of fluoride salt, fluorotitanate and sodium phosphate; 3) Micro-arc oxidation treatment: a) Low voltage passivation; b) High voltage growth.

5. The preparation method according to claim 4, characterized in that: The micro-arc oxidation treatment in a) and b) includes a one-step treatment, or a step-by-step pressure-boosting treatment by only changing the voltage; The voltage span of the segmented or stepped treatment is at least 20V; the stepped treatment refers to the treatment of only increasing the forward voltage step by step; the segmented treatment refers to the change of parameters such as frequency and duty cycle in addition to increasing the forward voltage step by step; The treatment time of each stage of the segmented treatment is 1 to 15 minutes, and the treatment time of each stage of the step-type treatment is 1 to 15 minutes; if a) and b) adopt segmented and step-type treatment, each stage should be at least 2 stages; after high voltage growth, voltage reduction repair is also carried out; The electrolyte temperature is not higher than 45°C during the micro-arc oxidation process.

6. The preparation method according to claim 4, characterized in that: Step 1) During the workpiece pretreatment, the magnesium / aluminum or alloy composite material workpiece is polished step by step with sandpaper to remove surface processing marks, and is ultrasonically cleaned in anhydrous ethanol for at least 6 minutes and blown dry for later use.

7. The preparation method according to claim 4, characterized in that: Step 2) When preparing the electrolyte, the concentration of sodium hydroxide is 5-50g / L, the concentration of tetraethyl silicate is 10-250ml / L, the solute addition order should be sodium hydroxide, tetraethyl silicate, and stirring should be maintained during the addition process; the solution should be continuously stirred for 1-12h after preparation; the concentration of the additive does not exceed 40g / L.

8. The preparation method according to claim 4, characterized in that: Step 3) Micro-arc oxidation treatment: a) Low voltage passivation: forward voltage 50~480V, negative voltage 0~200V, current density 1~20A / dm 2 , frequency is 50~5000Hz, duty cycle is 5%~50%, positive and negative pulse number ratio is (1~10):(0~10), processing time is 5~30min; positive and negative directions adopt constant voltage or constant current mode output; b) High voltage growth: forward voltage 400-600V, negative voltage 0-200V, current density 1-20A / dm 2 , frequency is 50~5000Hz, duty cycle is 5%~50%, the ratio of positive and negative pulse numbers is (1~10):(0~10), processing time is 3~30min; positive and negative directions adopt constant voltage or constant current mode output.

9. The preparation method according to claim 5, characterized in that: Voltage reduction repair: forward voltage 300~500V, negative voltage 0~200V, current density 1~20A / dm 2 , frequency is 50~5000Hz, duty cycle is 5%~50%, the ratio of positive and negative pulse numbers is (1~10):(0~10), processing time is 3~30min; positive and negative directions adopt constant voltage or constant current mode output.

10. Use of the micro-arc oxidation coating on the surface of the magnesium / aluminum or its alloy composite material according to any one of claims 1 to 3, or the micro-arc oxidation coating on the surface of the magnesium / aluminum or its alloy composite material prepared by the method according to any one of claims 4 to 9 in metal corrosion protection.

Citation Information

Patent Citations

  • A micro-arc oxidation film on the surface of an aluminum / titanium composite plate and a preparation method thereof

    CN104846412B

  • Amorphous silicon dioxide coating prepared based on micro-arc oxidation as well as preparation method and application of amorphous silicon dioxide coating

    CN116497419A

Cited By

  • Comprehensive protection method for preventing galvanic corrosion of magnesium alloy

    CN122169094A